38.1k views
5 votes
Given f(x)= 2^x and g(x)=x+1, (f*g)(x)

2 Answers

3 votes

Answer:


(f\cdot g)(x)=x \cdot 2^x+2^x

Now if you meant to have an open circle that would lead to a totally different answer. So if that is the case, I need to know. Thank you kindly.

Explanation:


(f\cdot g)(x)=f(x) \cdot g(x)


(f\cdot g)(x)=(2^x)\cdot(x+1) (Plugging in the given expressions)


(f\cdot g)(x)=2^x \cdot x+2^x \cdot 1 (By distributive property)


(f\cdot g)(x)=x \cdot 2^x+2^x (By commutative and identity property)

User Ihightower
by
4.4k points
3 votes

Answer:

x2ˣ + 2ˣ

Explanation:

Points to remember

(f * g)(x) = f(x) * g(x)

It is given that, f(x)= 2ˣ and g(x)=x+1

To find the value of (f * g)(x)

Let f(x)= 2ˣ and g(x) = x + 1

(f * g)(x) = f(x) * g(x)

= (2ˣ )* (x + 1)

= (2ˣ * x) + ( 2ˣ * 1)

= x2ˣ + 2ˣ

User Sebi
by
4.4k points